Lower Urinary Tract Infection and Bacterial Colonization in Patient with Double J Ureteral Stent - Joshi, R; Singh, D R; Sharma, S (Journal of Nepal Health Research Council, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE NE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Background: The aim of this study is to investigate the bacteriology of urinary tract infection associated with indwelling DJ stent. Methods: A total of 60 patients were included and 14 lost during follow up. Study period was for 6 months carried out in the department of surgery, Kathmandu Medical College. Prophylactic antibiotic was given at the time of intervention. Mid stream urine samples for routine and culture were sent before intervention. Urine samples during DJ removal and DJ tip cultures were also sent.All patients were â€œstentedâ€ during the various open and endourolgical procedures. Patients were clinically followed for a period till the DJ was removed. Statistical Package for Scientific Study (SPSS) 11, Chi square Test was used for statistical analysis. Results: A total of 46 cases were included. Mean age in years was 35.70 (10- 78years).Male were 22 and female 24. Eleven patients (23.91%) had stent placed less than 30 days and 35 patients (76.08%) had it for equal or more than 30 days. DJ indwelling time was in between 12-86 days.Bacterial colonies were found in 28.3% (13 of 46) of the urine samples and 30.4% (14 of 46) from thetip of the DJ stent segment.Of the pathogens identified, E. coli was found to be the most common.An increased stent colonization rate was associated with implantation time, female sex.On urine culture 70.21% had no growth, 14.89% E. coli, 4.25% Klebsiella, Actinobacter,2.12% Ecoli/kleb, multiple org, psuedomonas.Ten patients (21.7%) hadpositive urine culture before stent insertion.Thirteen patients (28.3%) were shown to have positive urine culture on stent removal. Fourteen patients (30.4%) had positive DJ stent culture. Conclusions: Positive urine culture and positive DJ tip cultures had strong correlation. Longer duration of placement of stent showed stent colonization. The commonest pathogen was E. Coli. Keywords: double J stent, escherichia coli.